2019
DOI: 10.1021/acsomega.9b01737
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Deoxygenation of the Oil and Biodiesel of Licuri (Syagrus coronata) To Obtain n-Alkanes with Chains in the Range of Biojet Fuels

Abstract: Aviation industry has the challenge of halving CO2 emissions by 2050, as compared to 2005. An alternative are drop-in biofuels, which are sustainable and fully compatible with aircraft engines and also can be mixed with fossil jet fuel. Among the feedstock for biojet fuel production, licuri (Syagrus coronata) can be highlighted as most of its fatty acids are in the jet fuel range. Thereby, this work investigated the composition and physicochemical characterization of licuri oil and licuri biodiesel, both with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
0
30
0
3
Order By: Relevance
“…Furthermore, a high hydrogenation activity of Pd/C was reported since all hydrocarbons formed were saturated [67]. Similarly, the Pd/C catalyst was employed for the deoxygenation of licuri (Syagrus coronata) oil and biodiesel, showing conversion to n-alkanes of 39.2 mol.% for licuri biodiesel at 207 psi of He (5% of H 2 ), 300 • C, 4 h and 1000 rpm [68]. The decarboxylation pathway is preferred as the production of n-alkanes occurs with the loss of the carboxyl group from the feedstock, as well as the selectivity to CO 2 being much higher than that to CO.…”
Section: Catalytic Hydrodeoxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a high hydrogenation activity of Pd/C was reported since all hydrocarbons formed were saturated [67]. Similarly, the Pd/C catalyst was employed for the deoxygenation of licuri (Syagrus coronata) oil and biodiesel, showing conversion to n-alkanes of 39.2 mol.% for licuri biodiesel at 207 psi of He (5% of H 2 ), 300 • C, 4 h and 1000 rpm [68]. The decarboxylation pathway is preferred as the production of n-alkanes occurs with the loss of the carboxyl group from the feedstock, as well as the selectivity to CO 2 being much higher than that to CO.…”
Section: Catalytic Hydrodeoxygenationmentioning
confidence: 99%
“…The decarboxylation pathway is preferred as the production of n-alkanes occurs with the loss of the carboxyl group from the feedstock, as well as the selectivity to CO 2 being much higher than that to CO. Moreover, it was reported that the increase in the number of carbon atoms in the feedstock chain enhances the catalytic deoxygenation process [68]. Overall, Pd was reported as an excellent catalyst for the formation of linear chain paraffin; however, its deactivation due to the poisoning of the active sites by adsorbed reaction intermediates (heavy organic substances, carbonaceous deposits and carbon monoxide, for example) and high cost renders it unfeasible for commercial use [69].…”
Section: Catalytic Hydrodeoxygenationmentioning
confidence: 99%
“…A large variety of feedstocks can be transformed into jet fuels by this route including fatty acids, TGs, vegetable oils [23][24][25], waste cooking oils [26,27], animal fats [28], and trapped greases [29], among others. Vegetable oils rich in fatty acids containing a high number of unsaturations such as camelina, jatropha, and algae-derived are particularly suitable for the production of jet fuels since these unsaturations facilitate the formation of branched hydrocarbons (with good cold-flow properties) during hydrotreating [30].…”
Section: Oil To Jet Fuelsmentioning
confidence: 99%
“…Ao longo dos anos algumas biomassas, a exemplo do pinhão-manso e da camelina, foram aproveitadas para a produção do BioQAV, sendo utilizadas, por diversas vezes, tanto em voos teste como em voos comerciais, se mostrando promissoras para uma futura implementação em voos regulares. O licuri, apesar de nunca ter sido testado pela aviação, têm se mostrado uma biomassa bastante promissora com potencial para a produção do bioquerosene (ARAÚJO et al, 2019) 3.2.1 Pinhão-manso O pinhão-manso é uma espécie de planta oleaginosa da família Euphorbiaceae, que apresenta um rápido crescimento atingindo uma altura entre 2 a 3 metros, podendo alcançar até 5 metros (ARRUDA et al, 2004). É considerada uma planta de fácil plantio e se ambienta com facilidade a diferentes climas, com ciclo produtivo de até 40 anos (FREIRE et al, 2010).…”
Section: Biomassasunclassified